Freedom and the law: yes or no to life? - StyczeÂ´n, Tadeusz (Medicina e Morale, 1997)
One of the ethics scholar's main ethical cultural duties, indicated by the encyclica Evangelium Vitae (EV), is to attempt to make all men conscious, as citizen of their countries, of how they transform their country as a legislator, and who they themselves become, when their country, with an act of positive law deprives of any protection by the law, as in the case of the legalisation of abortion, those who are killed in order to protect and even support, with the same act, those who kill theme. In this perspective the author analyses these kinds of laws in the light of the EV. The author first concentrates on men and then on the institutions they create: law and the State, and he examines their "human", that is cultural dimension. The dramatic aspect of the diagnosis presented by the EV can be seen in the progressive expansion of the "culture of death". Proof of this is the fact that the UN. Was founded in order to overcome the first case in the history of humanity of a law against life"(the so-called Nuremberg decrees). However, in correspondence with the 50th anniversary of its existence, it is promoting the second case of a "law against life", the "right to safe abortion". The author concentrateson the destruction of culture like the culture of death and aims to carry out a more differentiated diagnosis of it, in order to provide suitable "therapies". Which is the only way to counter and prevent the phenomenon of the dying out of human culture.